Analisis Komparatif Konsep Ba'i, Tijarah, Khiyar Dalam Perspektif Empat Mazhab: Implikasi Terhadap Transaksi Ekonomi Modern - Sulaeman; Jubaedah, Dedah (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2025)
This study examines the concepts of ba'i, tijarah, and khiyar from the perspective of four major schools of Islamic jurisprudence (Hanafi, Maliki, Shafi'i, and Hanbali) and their implications for modern economic transactions. The complexity of contemporary transactions and variations in fiqh muamalah interpretations among schools create challenges in harmonizing Islamic financial practices. Using a qualitative approach with content analysis method, this research analyzes classical fiqh literature and contemporary sources to identify similarities and differences in interpretations among the four schools. The findings reveal that the diversity of views among schools provides flexibility in developing modern Islamic financial products while maintaining fundamental sharia principles. The Hanafi and Hanbali schools tend to be more flexible in responding to transactional innovations, while the Maliki and Shafi'i schools emphasize prudential aspects and consumer protection. This research contributes to developing a theoretical framework that accommodates the diversity of fiqh interpretations in the modern economic context.